Pengaruh Kompensasi Terhadap Kepuasan Kerja Karyawan Pada Divisi Manufactur PT. Prima Medika Laboratories Tangerang - Wulan Ariani Damayanti; Emma Julianti (CV. Ulil Albab Corp, 2024)
The level of Employee job satisfaction in organisation is an individual thing because each individual has a different level of satisfaction based on the values that apply to him, but whether or not the level of job satisfaction is increased depends on whether the remuneration (compensation) received by employees is in accordance with expectations, needs, and wants of employee. The purpose of this study was to determine how compensation, employee job satisfaction, and the effect of compensation on employee job satisfaction in the manufacturing division at PT. Prima Medika Laboratories Tangerang. The research method is descriptive analysis using a quantitative approach, with a simple random sampling technique of 55 employees of the manufacturing division as respondents, and information handling is completed utilizing SPSS V.26 programming. Compensation and job satisfaction of employees at this company show good results, all data in this study are valid and reliable with the results of simple linear regression analysis show that compensation has a positive contribution in influencing employee job satisfaction by 74.5%, has a strong relationship, and compensation has a 60.3% on employee job satisfaction at PT. Prima Medika Laboratories Tangerang, with the remaining 39.7% influenced by variables other than those used in this study.